Institutional Change, Entrepreneuring and Place: Building a Smart State. Issue 2 (February 2022) - Staggs, Jonathan; Wright, April L.; Jarvis, Lee
We shed new light on the processes through which institutions are created and changed by investigating the question how does institutional entrepreneuring unfold in an already organized world. We conducted a longitudinal case study of the field of scientific research production in Australia, which changed over three decades through entrepreneuring processes associated with the creation of a new 'Smart State' place in the city of Brisbane in Queensland. A new place is a form of organizing human activity that has materiality and meaning at a specific geographic location. Our findings showed how field change was interwoven with place creation through four processes of entrepreneuring: structural emancipation, dissociating and reimagining place meanings, bricolaging of place forms and co-evolving place identities. These entrepreneuring processes constituted the field as a flow of 'becoming' that spilled over into temporary and provisional settlements in local places. Our findings make important contributions through: (1) deepening understanding of how organizational fields change through multilevel, distributed, cascading and often unreflexive processes of entrepreneuring in an already organized world; (2) bringing attention to a relationship between institutions and place, in which place is both the medium and outcome of institutional entrepreneuring; and (3) providing new insight into embedded agency by illustrating how institutions in 'becoming' continually (re)produce the resources and possibilities for agency within gradual institutional change over time.